Youth wellness promotion for development of positive dietary and physical activity behaviors - Cull, Brooke J. (Kansas State University, 2017)
This dissertation examined the impact of wellness-promotion interventions on health-related behaviors in youth, including dietary intake and physical activity (PA) levels. Additionally, the impact of wellness-promotion interventions on health-promoting opportunities for youth in an out-of-school setting was investigated. In study 1 (Chapter 2), the feasibility and preliminary impact of a 12-week, home-based wellness coaching intervention for changes in behavioral, psychosocial, and biomedical outcomes in normal-weight female children was evaluated. The two intervention conditions included a general health education condition, and one that implemented skills-building components in the areas of PA and healthy eating. Results showed that both intervention conditions were feasible and well-accepted by participants. There were no changes in the behavioral outcomes of PA levels or fruit and vegetable (FV) consumption, but girls who received the skills-building coaching condition showed an increase in emotional quality of life and a reduction in body fat percentage. Findings suggested that a home-based wellness coaching intervention was feasible and was potentially effective for impacting psychosocial and biomedical outcomes in normal-weight female children. Study 2 (Chapter 3) examined the impact of Girl Scout leader wellness training on implementation of wellness-promoting practices and opportunities for girls during troop meetings. This study compared the effectiveness of in-person versus online leader wellness training, specifically assessing opportunities for wellness-promoting behaviors, including FV consumption and PA during meetings. Study results indicated that leaders who received the wellness training in person increased their implementation of wellness-promoting practices significantly more than those who received the wellness training in an online format. Analyses regarding dissemination revealed that adoption of wellness-training principles occurred in approximately 43% of troop leaders, and that lower-income leaders were more interested in receiving the wellness training, as compared to higher-income leaders. Overall, results indicated that in-person wellness training was effective for improving wellness-promoting opportunities for girls, but a more cost-effective and further-reaching training method was needed for a larger public health impact. Therefore, study 3 (Chapter 4) evaluated the impact of online, video-based wellness training on Girl Scout leaders’ wellness-promotion self-efficacy, intention, and knowledge. These factors are established determinants of behavior change, including offering opportunities in the areas of PA and FV consumption. Results showed that leaders who received the video-based wellness training had a significant increase in self-efficacy for overcoming barriers related to PA and FV practices, as well as increased self-efficacy for offering vegetables during troop meetings. Both groups showed increased intention for offering both fruit and vegetable opportunities during upcoming meetings. These results showed that online, video-based wellness training was effective for impacting determinants of behavior change in Girl Scout troop leaders, which may improve the wellness opportunities for girls during troop meetings. Overall, the findings from this dissertation collectively contribute to the existing literature by providing evidence regarding effective interventions for improving wellness-promoting opportunities and experiences for youth. If disseminated and implemented widely, evidence-based interventions and practices similar to those discussed within this dissertation may lead to improvements in health-related behaviors among youth, increased wellness-promoting opportunities, and ultimately have a positive impact on population health.
Keywords: Wellness promotion; Nutrition; Physical activity; Public health